(untitled) (Gaceta Técnica, 2022)
The present study describes the structural evaluation of an informally built reinforced concrete house in Ecuador, which has several structural pathologies. As a starting point, problems were identified, the causes were analyzed and a diagnosis of the current state was formulated. Subsequently, an analytical study of the house reinforced with the veneer system was carried out, as well as the reference budget that this reinforcement would have. The results that were obtained demonstrate the effectiveness of the system since it provides rigidity and resistance to the structure, making it comply with the earthquake-resistant philosophy at a low cost